2021
DOI: 10.1093/eurheartj/ehab724.2360
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of non-dipping patterns among black Africans with uncontrolled hypertension: a secondary analysis of the CREOLE trial

Abstract: Background Dipping of blood pressure (BP) at night is a normal physiological phenomenon. However, a non-dipping pattern is associated with hypertension mediated organ damage, secondary forms of hypertension and poorer long-term outcome. Identifying a non-dipping pattern may be useful in assessing risk, aiding the decision to investigate for secondary causes, initiating treatment, assisting decisions on choice and timing of anti-hypertensive therapy, and intensifying salt restriction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In an analysis from the CREOLE study, which included 721 Black people from sub-Saharan Africa between 30 and 79 years of age with uncontrolled hypertension and a baseline 24-h ambulatory BP monitoring, the prevalence of nondipping pattern was 78%. 117…”
Section: High Blood Pressurementioning
confidence: 99%
“…In an analysis from the CREOLE study, which included 721 Black people from sub-Saharan Africa between 30 and 79 years of age with uncontrolled hypertension and a baseline 24-h ambulatory BP monitoring, the prevalence of nondipping pattern was 78%. 117…”
Section: High Blood Pressurementioning
confidence: 99%
“…While nocturnal BP dipping may impact on 24-hour BP variability, 26 it is reassuring that 78% of CREOLE participants were classified as nondippers 27 and similar low degrees of dipping occurred across all 3 groups of patients. Consequently, we did not apply a weighted SD to adjust for night-time falls.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals are forced to consume a high salt diet due to their inability to access healthy, natural food options. A study by Ingabire et al further examined the rates of non-dipping patterns across ethnicities, and found that non-dippers were more likely to be African American, specifically, those with uncontrolled hypertension (Ingabire et al, 2021). Furthermore, African Americans were found to have a higher percentage of patients expressing a non-dipping pattern (Muntner et al, 2015).…”
Section: Social Differences In Food Availability Led To Differences I...mentioning
confidence: 99%